2015
DOI: 10.1111/cpr.12174
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor STOX1 regulates proliferation of inner ear epithelial cells via the AKT pathway

Abstract: Taken together, we demonstrate that STOX1 is a novel stimulatory factor for inner ear epithelial cell proliferation and might be an important target to be considered in regeneration or repair of inner ear epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Thus, we focused on Stox1. Stox1 is a transcription factor belonging to the enlarged Forkhead Box gene family that has been associated with preeclampsia (van Dijk et al, ), central nervous system (Abel, Abdul‐Hamid, Dijk, & Oudejans, ; Feng et al, ) and inner ear epithelial cells development (Nie et al, ), palys a significant role in cell proliferation and migration (Nie et al, ; van Dijk et al, ). Second, it is reported that there are endothelial cell dysfunction and cardiac hypertrophy in the Stox1 model of preeclampsia (Ducat et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we focused on Stox1. Stox1 is a transcription factor belonging to the enlarged Forkhead Box gene family that has been associated with preeclampsia (van Dijk et al, ), central nervous system (Abel, Abdul‐Hamid, Dijk, & Oudejans, ; Feng et al, ) and inner ear epithelial cells development (Nie et al, ), palys a significant role in cell proliferation and migration (Nie et al, ; van Dijk et al, ). Second, it is reported that there are endothelial cell dysfunction and cardiac hypertrophy in the Stox1 model of preeclampsia (Ducat et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Gata2 is critical for vestibular organ morphogenesis ( Haugas et al, 2010 ). Stox1 is selectively expressed in the cochlear sensory epithelium, and overexpression of Stox1 enhances cell proliferation and sphere formation ( Nie et al, 2015 ), suggesting that Stox1 might be one of the genes leading to the greater proliferation ability of Lgr5+ progenitors. Genes highly expressed in Lgr6+ progenitors compared to Lgr5+ progenitors include Adk and Otoa .…”
Section: Discussionmentioning
confidence: 99%
“…Doridot L et al have found that STOX1 can play a genetic switch in the nitroso-redox balance and mitochondrial homeostasis (Doridot et al, 2014). Furthermore, STOX1 was also found to involve inner ear epithelial cell proliferation as a novel stimulatory factor activated by phosphorylation of protein kinase B pathway (Nie et al, 2015). LDH is a degenerative disease related F I G U R E 1 Haplotype block map for part of the SNPs in the STOX1.…”
Section: Discussionmentioning
confidence: 99%